2019
DOI: 10.1097/aln.0000000000002626
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Severity, and Detection of Blood Pressure Perturbations after Abdominal Surgery

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Intraoperative and postoperative hypotension are associated with myocardial and kidney injury and 30-day mortality. Intraoperative blood pressure is measured frequently, but blood pressure on surgical wards is usually me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 27 publications
(16 reference statements)
2
93
0
Order By: Relevance
“…Studies that obtained continuous pulse oximetry and blood pressure readings from patients on surgical floors have shown that many patients have prolonged hypoxia and hypotension that is not identified by health care providers. 22,23 Given that some studies have shown that hypoxia and hypotension are precursors to postoperative complications, 24,25 remote automated monitoring technology with a health care provider who is available to respond to early signs of an impending complication may improve outcomes after surgery, similar to how anesthesiologists and enhanced monitoring improved intraoperative outcomes. These interventions require evaluation in prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that obtained continuous pulse oximetry and blood pressure readings from patients on surgical floors have shown that many patients have prolonged hypoxia and hypotension that is not identified by health care providers. 22,23 Given that some studies have shown that hypoxia and hypotension are precursors to postoperative complications, 24,25 remote automated monitoring technology with a health care provider who is available to respond to early signs of an impending complication may improve outcomes after surgery, similar to how anesthesiologists and enhanced monitoring improved intraoperative outcomes. These interventions require evaluation in prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…(25) Moreover, it seems likely, that postoperative NT-proBNP concentration might be affected by several perioperative factors such as surgical stress, hemodynamic perturbations, or in ammation rather than by uid management alone. (26)(27)(28) We further evaluated the effect of colloids versus crystalloids on the incidence of MINS. We hypothesized that patients receiving colloids had a better hemodynamic stability, which might result in an improved myocardial perfusion and consequently in lower postoperative troponin T concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well known that postoperative hypotension is common and that it is as an important risk factor for MINS (28,29). Thus, it is likely that postoperative hypotension was associated with MINS.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, this means that for most hospitalized patients, BP is monitored using intermittent cuff-based measurements. The interval between measurements may be several hours, and a recent publication found that a substantial proportion of significant BP-perturbations may go undetected with standard monitoring [2]. This implies that continuous non-invasive BP-monitoring (cNIBP) could benefit patients who are not candidates for arterial line placement.…”
Section: Introductionmentioning
confidence: 99%